Nanopore Sequencing for Detection and Characterization of Phosphorothioate Modifications in Native DNA Sequences - Wadley, Taylor; Moon, Sun Hee; DeMott, Michael S.; Wanchai, Visanu; Huang, En; Dedon, Peter C.; Boysen, Gunnar; Nookaew, Intawat (Frontiers in Microbiology, 2022)
Bacterial DNA is subject to various modifications involved in gene regulation and defense against bacteriophage attacks. Phosphorothioate (PT) modifications are protective modifications in which the non-bridging oxygen in the DNA phosphate backbone is replaced with a sulfur atom. Here, we expand third-generation sequencing techniques to allow for the sequence-specific mapping of DNA modifications by demonstrating the application of Oxford Nanopore Technologies (ONT) and the ELIGOS software package for site-specific detection and characterization of PT modifications. The ONT/ELIGOS platform accurately detected PT modifications in a plasmid carrying synthetic PT modifications. Subsequently, studies were extended to the genome-wide mapping of PT modifications in the Salmonella enterica genomes within the wild-type strain and strains lacking the PT regulatory gene dndB (ΔdndB) or the PT synthetic gene dndC (ΔdndC). PT site-specific signatures were observed in the established motifs of GAAC/GTTC. The PT site locations were in close agreement with PT sites previously identified using the Nick-seq technique. Compared to the wild-type strain, the number of PT modifications are 1.8-fold higher in ΔdndB and 25-fold lower in ΔdndC, again consistent with known regulation of the dnd operon. These results demonstrate the suitability of the ONT platform for accurate detection and identification of the unusual PT backbone modifications in native genome sequences.